Ripple effects mapping: capturing the wider impacts of systems change efforts in public health - and Nobles, James; Wheeler, Jessica; Dunleavy-Harris, Kirsty; Holmes, Richard; Inman-Ward, Alan; Potts, Alexandra; Hall, Jennifer; Redwood, Sabi; Jago, Russell; Foster, Charlie (BMC Medical Research Methodology, 2022)
Systems approaches are currently being advocated and implemented to address complex challenges in Public Health. These approaches work by bringing multi-sectoral stakeholders together to develop a collective understanding of the system, and then to identify places where they can leverage change across the system. Systems approaches are unpredictable, where cause-and-effect cannot always be disentangled, and unintended consequences – positive and negative – frequently arise. Evaluating such approaches is difficult and new methods are warranted.
Keywords: Complex adaptive systems; Complexity; Evaluation; Public health; Systems approach; Systems science